Consistent and Contrasting Aspects of the Geomagnetic Field Across Epochs With Distinct Reversal Frequencies Revealed by Modeling the Kiaman Superchron. (29th June 2021) - Brandt, Daniele; Ernesto, Marcia; Constable, Catherine
Abstract: This work presents an extensive directional paleomagnetic database of the Kiaman reversed superchron. It is composed of 1, 459 paleomagnetic directions from igneous rocks corresponding to 91 data sets (or paleomagnetic poles). An almost constant behavior of more concentrated and circular distributions for latitudes higher than 10° was found, which contrasts strongly with predictions of the representative models for the past few million years. We searched for simplified and spatially covariant Giant Gaussian Process (GGP) models that best explain the directional distribution of the Kiaman database. We used the mean strength based on the mean of virtual dipole moment (VDM) results for the period drawn from the available databases. Among the tested models, the one that best explains the directional paleosecular variation of the Kiaman database is the covariant type. According to this model, the correlations between the Gaussian coefficients are valid for the last 10 Myr and the Kiaman superchron. The resulting GGP models have β parameters similar to the 0–10 Ma models, which indicates that the relation between symmetric and antisymmetric families appears unchanged in the geological past. The relative variability of the Kiaman field, as inferred from the ratio α g 1 0 ¯ from GGP models, is lower than for the past 10 Myr. Thus, as well as the paleointensity, α g 1 0 ¯ seems to be a proxy that can be used for evaluating the geomagnetic development along the geological time. Key Points: A new database of paleomagnetic directions of igneous Kiaman sites The distributions of the Kiaman directions reveal low paleosecular variation The first Giant Gaussian Process models for ages older than the last 10 million years are presented